ANALYSIS AND EFFICIENCY OF A GADOLINIUM MAGNETOCALORIC MATERIAL PLATE - Dorin, Botoc; Ionut-Bogdan, Rusu; Adrian, Plesca; Jurij, Avsec (Journal of Energy Technology, 2024)
In this article, the influence of a controlled magnetic field on gadolinium plates was modelled and simulated to be used in magnetic refrigeration installations. This is a state-of-the-art technology that does not use refrigerants and does not work based on vapour compression, which is based on the operation of the magnetocaloric properties of the material used; in the case below, this material, in the form of a flat plate, has certain magnetocaloric properties and under the influence of magnetic induction can be used successfully in such innovative installations. The advantages of using gadolinium in the form of a flat plate in a magnetic regenerator and thermal energy dissipation on its surface under the controlled magnetic field’s influence were studied.